2009
DOI: 10.1093/rheumatology/kep388
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, physically demanding work and traumatic knee injury are major risk factors for knee osteoarthritis--a population-based study with a follow-up of 22 years

Abstract: This prospective study confirms the roles of obesity, heavy work load and knee injury in the aetiology of knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 27 publications
9
106
0
16
Order By: Relevance
“…For instance, the association between work load and increased risk of knee OA was demonstrated in Ref. [23,24] Also, a physically heavy workload was shown to be detrimental to the knee joint and to increase the risk of severe OA. [7] Finally, it was shown that prolonged or repeated knee bending is a risk factor for knee OA, and that risk may be higher in jobs involving knee bending and mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the association between work load and increased risk of knee OA was demonstrated in Ref. [23,24] Also, a physically heavy workload was shown to be detrimental to the knee joint and to increase the risk of severe OA. [7] Finally, it was shown that prolonged or repeated knee bending is a risk factor for knee OA, and that risk may be higher in jobs involving knee bending and mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…According to the most recent estimates by the World Health Organization, 35% of all adults are overweight (body mass index [BMI] $25 kg/m 2 ) and more than 12% are obese (BMI $30 kg/m 2 ) (1). A high BMI is a strong risk factor for the onset of knee osteoarthritis (OA) (2)(3)(4) and has been associated with the incidence of both clinical (5-7) and structural (8)(9)(10)(11)(12)(13) features of knee OA. Given the high medical costs, productivity costs, morbidity, and disability associated with knee OA, there is an increasing need for preventive measures (14).…”
Section: Introductionmentioning
confidence: 99%
“…The association of knee osteoarthritis with occupational kneeling and squatting has been shown to increase 7-fold between the lowest and highest categories of BMI (69,70). The impact of heavy workload, obesity, and traumatic knee injuries on the development of osteoarthritis have been reported from a prospective study of a Finnish cohort with ≥20 years of follow-up (71). The combined impact of kneeling/ squatting activities and obesity may also be important for the progression of existing knee osteoarthritis symptoms (72)(73)(74).…”
mentioning
confidence: 99%